Feminine mystique and the patriarchal world in Tillie Olsen's I Stand Here Ironing - Ahmad Jafni, Nur Fatin Syuhada; Bahar, Ida Baizura (Universiti Putra Malaysia Press, 2014)
This paper examines the relationship between women and men and how the women had to live, behave and react in 1960s America in the short story “I Stand Here Ironing” (1961) by the twentieth-century American author, Tillie Olsen (1912-2007). The story revolves around the protagonist, ‘mother’, and her daughter, Emily, where the women are depicted as confined within constrained identities, having to live in a world where they have to be obedient and having to live up to men’s expectation. With the pressure enforced by the expectations of the patriarchal society and the idea of ‘feminine mystique’, the women seem to be devoid of any romantic feelings. Based on a textual analysis as our methodology, our study focuses on women’s position in the second wave feminism period by using the feminist concept of the feminine mystique, as the conceptual framework, as outlined by Betty Friedan in her book, The Feminine Mystique (1963). Our findings demonstrate that the reasons behind the female protagonist’s barren emotions for men are because of her sense of obligations on completing the domestic demands, the expectations set by the patriarchal society and because of the judgemental eyes of the men in the patriarchal society in general.